Analysis of Technology Acceptance Model (TAM) Approach Towards Repeat Purchases With User Satisfaction Mediation on Cinepolis Application Using SEM-PLS Method - Rafael Adhi Wicaksono; Safirin, Moch Tutuk (Dinasti International Journal of Economics, Finance & Accounting, 2025)
Technological advances encourage companies to present easy and useful service applications. The Cinepolis application is considered not optimal, as seen from negative ratings and reviews. This research examines how perceived usefulness, ease of use, benefits, features, and trust influence repeat purchase behavior, with user satisfaction serving as a mediating variable. The study employs the SEM-PLS method and involves 100 respondents who are users of the Cinepolis application. The findings indicate that all the independent variables significantly impact repeat purchase decisions, except for the mediation of perceived ease through user satisfaction which was not significant. Cinepolis is advised to improve user benefits, features, and trust to encourage satisfaction and repeat purchases.